Influence Of Parallel Evolving Microstructure On Thermal Diffusivity In Strontium Titanate - Idza Riati Ibrahim; Mansor Hashim; Zaidan Abdul Wahab; Khamirul Amin Matori; Rodziah Nazlan; Ismayadi Ismail; Nor Hapishah Abdullah; Wan Norailiana Wan Ab Rahman; Fadzidah Mohd Idris (Trans Tech Publication, 2024)
Indexed by SCOPUS